Corporate Memory Records and Information Management in the Knowledge Age - Megill, Kenneth A. (K. G. Saur, 2005)
Corporate memory' is the body of information that an organization needs to keep for re-use. It is the active and historical information that an organization has that is worth sharing, managing and preserving to enable it to function effectively. This book is aimed at records managers and archivists, who are responsible for maintaining and managing information within an organization. It describes fully the most up-to-date methods and approaches to this essential function. In addition, it also discusses the adoption of an international standard for record management.